Comparison of levobupivacaine with ropivacaine for supraclavicular brachial plexus block - Kulkarni, Shantanu B.; Pimpare, Meena; Govardhane, Balasaheb T. (International Journal of Research in Medical Sciences, 2016)
Background: Peripheral nerve blocks have assumed a prominent role in modern anaesthesia practice as they provide ideal operative conditions without any general anaesthesia or adverse haemodynamic effects. When compared with ropivacaine, levobupivacaine is a newer, safer, longer acting local anaesthetic with rapid onset and prolonged duration of analgesia and similar or more pronounced nerve blocking effects, depending on the concentration. Hence the present study is aimed to compare the effectiveness of 0.5% levobupivacaine and 0.5% ropivacaine in supraclavicular brachial plexus block. Methods: The present study was a prospective, randomized, double blind comparative study of 60 patients with ASA grade I, II of either sex, between the ages 18 years to 60 years. They were enrolled and randomly divided into two groups. Supraclavicular brachial plexus block was given for upper limb surgeries using 0.5% levobupivacaine (Group L) or 0.5% ropivacaine (Group R). The onset of sensory and motor block, their duration, and possible adverse events were recorded and compared for both groups. Results: Significant earlier onset of sensory blockade (p=0.027) and motor blockade (p=0.01), prolonged duration of sensory and motor blockade (p=0.0001) was observed in group of patients receiving levobupivacaine compared to ropivacaine. The time for first rescue analgesia required post operatively was much longer in Group L(13.2333±1.1651hr) as compared to Group R(10.8667±0.91852 hr) and the difference was significant (p=0.0001).Intraoperatively throughout the study heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were comparable in both the groups and found no statistically significant difference (p >0.05). The heart rate, systolic and diastolic blood pressure for both the groups were compared postoperatively and observed no statistical significant difference (p >0.05). No adverse effects were observed in both the groups. Conclusions: 0.5% levobupivacaine used in supraclavicular brachial plexus block for upper limb surgeries provides rapid onset of sensory and motor blockade and prolonged duration of analgesia compared to 0.5% ropivacaine.